Nutrilite green trim® reduced body weight, waist circumference, and body fat percentage in obese men with moderate physical exercise and low-calorie diet - Romy Kamaluddin; Wimpie Pangkahila; Alex Pangkahila (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2021)
Introduction: Management of obesity are including consumption of supplements. Nutrilite GreenTrim® Supplement contains green tea extract and EGCG and squalene. This study aimed to prove the effects of Nutrilite GreenTrim® on body weight, waist circumference, and body fats percentage in obese men. Methods: This clinical trial used pretest-posttest control group design in 22 obese men, aged 25-40 years with a BMI 25-35 kg/m2. Subjects were divided into the control group (K) and the treatment group (P). Subjects were given moderate physical exercise and a low-calorie diet. Results: The results showed K group lost weight (from 85.1±8.99 to 82.3±9.21 kg; p<0.001), while the P group lost weight (from 84.1±10.7 to 80.1±10.9 kg; p <0.001) and the difference showed that the P group lost weight greater than the K group (p = 0.007). K group experienced a decrease in waist circumference (from 96.9±7.69 to 93.8±8.84 cm; p <0.001), while the P group (from 96.5±7.78 to 92.2±7.59 cm; p <0.001) the difference showed that the decrease in waist circumference in the P group was better than the K group (p = 0.041). In the K group, body fat percentage decreased (from 27.5±3.31 to 25.8±3.77%; p <0.001), the P group also decreased (from 26.5±3.78 to 23.3±3.67%; p<0.001) the analysis showed that the decrease in body fat percentage in the P group was better than the K group (p <0.001). Conclusion: Supplementation of Nutrilite Green Trim® reduced body weight, waist circumference, and body fats percentage in obese men with moderate physical exercise and low-calorie diet.